2016
DOI: 10.1177/1098611116657283
|View full text |Cite
|
Sign up to set email alerts
|

Working Together or Working on the Same Task but Separately? A Comparison of Police Chief and Chief Probation or Parole Officer Perceptions of Partnership

Abstract: It remains unclear how pervasive police-community corrections partnerships are, and to what extent they are integrated into routine practice, as well as whether or not police chiefs and chief probation or parole officers within the same jurisdictions perceive them to be effective. The current study enhances our understanding of such partnerships between police and probation or parole. Data were collected through a statewide survey of a random sample of municipal police chiefs and county chief probation or paro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…Even if the benefits of such partnerships might not be directly crime-related in the short term, they can increase community satisfaction and police legitimacy which ultimately lead to long-term increases in compliance with the law (Telep & Weisburd, 2016). Of the interagency partnerships in the criminal justice field, the concept of police-probation partnerships has grown in popularity in response to a greater need for proactive supervision of probationers (Kim, Matz, & Lee, 2017). Beginning in the mid-1990s, police and probation officers began to collaborate informally on work (Parent & Snyder, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Even if the benefits of such partnerships might not be directly crime-related in the short term, they can increase community satisfaction and police legitimacy which ultimately lead to long-term increases in compliance with the law (Telep & Weisburd, 2016). Of the interagency partnerships in the criminal justice field, the concept of police-probation partnerships has grown in popularity in response to a greater need for proactive supervision of probationers (Kim, Matz, & Lee, 2017). Beginning in the mid-1990s, police and probation officers began to collaborate informally on work (Parent & Snyder, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Formalized police-probation/parole partnerships reached prominence in the mid-to-late 1990s as a consequence of the perceived success of Boston's Operation Night Light (Beto, 2005;Matz and Kim, 2016). However, recent studies have shown that the overwhelming majority of partnerships were based on individual relationships and were informal in nature, limited largely to periodic information sharing (Kim et al, 2017). The persistence of informal partnerships, or no partnerships at all, as opposed to formal partnerships, was consistent for both law enforcement studies (Kim et al, 2010; and the study of probation and parole agencies (Beto, 2005;Matz, 2016a).…”
Section: Introductionmentioning
confidence: 88%
“…What made Operation Night Light unique was that it went beyond personal relationships and became a collaborative model embraced by a number of agencies and stakeholder organizations (Beto, 2005;Fitzgerald, 2006). Formalizing such informal working relationships between police and community corrections officers, officially sanctioning them at the organizational level, and engendering a commitment on behalf of both agencies in a more formal sophisticated set of partnerships, has proven to be important in reducing the potential for unintended negative consequences (Jannetta and Lachman, 2011;Kim et al, 2010Kim et al, , 2017Murphy, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Parent and Snyder's (1999) early research examined a variety of policeprobation/partnerships and grouped these partnerships into categories based on similar goals and objectives. These findings served to inform a taxonomy of partnerships used extensively in subsequent surveys (Kim & Gerber, 2018;Kim et al, 2010;Kim, Matz et al, 2013;Kim, Matz, & Gerber, 2017;Kim, Matz, & Lee, 2017;Matz, 2016;. These partnership categorizations include enhanced supervision, information sharing, fugitive apprehension, specialized enforcement, and interagency problemsolving partnerships.…”
Section: The Prevalence Of Community Supervisionmentioning
confidence: 97%
“…These categorizations have guided several surveys administered by the Center for Project Spotlight in Texas (Kim et al, 2010) and later Pennsylvania (Kim, Matz, & Lee, 2017). These researchers were interested in understanding to what extent partnerships persisted despite the lack of federal or state funding support.…”
Section: Origins Of a Partnership Taxonomymentioning
confidence: 99%